Pengaruh Kepemimpinan Transformasional Terhadap Kinerja Melalui Adversity Resilience dan Kepuasan Kerja Pegawai Kantor Kelurahan se-Kecamatan Serang Kota - Baihaki, Baihaki; Basrowi, Basrowi; Khaeruman, Khaeruman (Universitas Lampung, 2024)
This research aims to analyze the influence of adversity resilience and transformational leadership on job satisfaction as well as the influence of transformational leadership on performance, both directly and through adversity resilience and job satisfaction. Apart from that, this research also examines the influence of adversity resilience and job satisfaction on the performance of sub-district office employees in Serang City, Banten Province. The approach used in this research is quantitative with a correlational design. The research population includes all sub-district office employees in Serang City spread across 12 sub-districts with a total of 187 people. The sample was determined using the Krejcie and Morgan Table, resulting in 108 respondents. Data collection was carried out through a questionnaire whose validity and reliability had been tested on 30 respondents. Data analysis uses Structural Equation Modeling (SEM), with evaluation of the outer model and inner model to ensure the validity and reliability of the instrument. The research results show that all hypotheses are accepted. Transformational leadership has a positive and significant effect on adversity resilience, job satisfaction and employee performance. Adversity resilience and job satisfaction also have a positive influence on employee performance. Apart from that, transformational leadership influences employee performance both directly and through the mediation of adversity resilience and job satisfaction. The implications of this research confirm that improving employee performance can be achieved by strengthening transformational leadership and increasing adversity resilience and job satisfaction. Therefore, sub-district heads and village heads are advised to implement more effective leadership strategies to encourage increased employee performance.Keywords: Adversity Resilience, Job Satisfaction, Employee Performance, SEM, Skill Improvement, Transformational Leadership